Implementation of the Use of Information and Communication Technology Media in Developing Career Awareness of An-Nur Ii Students "Al-Murtadlo" Bululawang Malang - Muhammad Bika Al Kavi (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
Information and communication technology is a basic human need today. But the IP-ICT index in Indonesia is still low in the sub-index of expertise in using ICT. Indonesia will receive the demographic bonus in 2030-2040. 64% of the people are residents of productive age, if they are not nurtured they will only become unemployed. Increasing skills in using ICT is a way out of these 2 problems. One of the appropriate institutions in improving these skills is the Islamic boarding school, although some Islamic boarding schools in Indonesia are still withdrawing from ICT. An-Nur II Al Murtadlo Islamic Boarding School has more attention on ICT science. all students, almost all of them belong to the pre-employment age group with different backgrounds, some of the things above underlie the author to carry out this research. The formulation of the problem, as well as the objectives of this research, are to find out 1) the implementation of the use of ICT media, 2) the specific strategy in its implementation, 3) the implications of the use of media and the career awareness of students. This type of research was conducted using a qualitative descriptive method with three data collection techniques, namely: observation, interviews, and documentation. While analyzing the data using data reduction, displaying data, and drawing conclusions. Research Results: 1) The implementation of the use of ICT media at An-Nur II in developing career awareness of students was carried out well, providing basic knowledge about ICT to students at the student level, then developing skills and applied practice, making the implementation process more organized and well sustainable. 2) The strategy, especially with the implementation of a reward system, then assignments in the realm of boarding school management with ICT elements, 3) The implications of using ICT media on the career awareness of students are considered to have a big influence, being initial capital and basic knowledge about careers in today's almost all of which are supported with ICT.